Ecology of Phyllodactylus angustidigitus and P. gerrhopygus (Squamata: Phyllodactylidae) from the Reserva Nacional de Paracas, Peru - Pérez Z., José (2011)
Until now, ecology of Phyllodactylus angustidigitus and P. gerrhopygus are unknown. In this work, we researched some aspects of P. angustidigitus and P. gerrhopygus niches at National Reserve of Paracas (RNP). We evaluated and compared: distribution, habitat use (spatial niche), activity patterns (temporal niche) and diet (trophic niche), all these aspects in both geckonids species. We estimated resource supply through pitfall traps. Paracas geckonid, P. angustidigitus, has been present in most of the RNP evaluated locations, and it was reported in desert and hills habitats. Southern geckonid, P. gerrhopygus, was reported only in Paracas peninsula and Sta. Cruz, in desert, hills and oasis habitats. Both species were founded in activity at night time. P. angustidigitus and P. gerrhopygus diet consisted in insects. The diet of these species shows a generalist behavior, caused by the trophic niche amplitude, and an opportunistic behavior, explained with similarity between diet composition and environment resource supply. Diet of both species was similar. Additionally the phylogenetic proximity between P. angustidigitus y P. gerrhopygus produces spatial niche similarities (habitat use) and temporal niche similarities (activity patterns) and trophic niche (diet). These important similarities in resources use can be derived in a potential competition of environmental resources between these simpatric geckonids. The information provided in this paper shows the need to design an appropriate strategy to ensure the conservation status of P. angustidigitus.